2022
DOI: 10.1177/00380407221139180
|View full text |Cite
|
Sign up to set email alerts
|

“As Diverse as Possible”: How Universities Compromise Multiracial Identities

Abstract: U.S. colleges and universities are under increasing pressure to appear racially diverse, but have yet to account systematically for a quickly growing contingent of multiracial-identifying students. Drawing on interviews with multiracial-identifying undergraduates at Western University, I demonstrate how everyday university practices compromise multiracial identities in the pursuit of diversity. The term compromise carries dual meaning, referring to instances where Western refashioned multiracial identities int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Additionally, selecting multiple race/ethnicity categories does not always equate with identifying as multiracial, and racial/ethnic identification is neither fixed nor objective (Ford et al, 2021; Talbot, 2008). While the diversity of students’ precollege educational context impacts multiracial claims (Burke & Kao, 2013), Giebel (2023) added that perceived university value of diversity may also impact how students report multiraciality in the college admissions process. Taken together, these findings suggest that a variety of factors impact the ways in which mixed-race students choose to self-categorize when applying to college and that this data is point-in-time rather than determinative of future self-labeling preferences.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, selecting multiple race/ethnicity categories does not always equate with identifying as multiracial, and racial/ethnic identification is neither fixed nor objective (Ford et al, 2021; Talbot, 2008). While the diversity of students’ precollege educational context impacts multiracial claims (Burke & Kao, 2013), Giebel (2023) added that perceived university value of diversity may also impact how students report multiraciality in the college admissions process. Taken together, these findings suggest that a variety of factors impact the ways in which mixed-race students choose to self-categorize when applying to college and that this data is point-in-time rather than determinative of future self-labeling preferences.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, it took a decade for the U.S. Department of Education and institutions of higher education to formally adopt and implement this guidance. As Giebel (2023) noted, students in the early 2000s had the option to select more than one race on the U.S. census but may not have been able to do so on their college applications. In a review of undergraduate admissions applications from 2002, Renn and Lunceford (2004) found that 62.2% of the 127 sampled institutions had not yet implemented OMB's 1997 updates.…”
mentioning
confidence: 99%
“…93 Linguistic ambiguity can also directly impact individuals' and populations' wellbeing; ironically, these consequences are often especially evident in racial equity programs, policy, and research. Diversity scholarships, recruitment and retention programs, and affinity groups frequently determine eligibility based on self-identified membership in a monoracial group 62,67,68 ; this framing may lead potential applicants who identify with one of these groups and with an noneligible group to doubt their overall eligibility. Indeed, empirical studies have shown that Biracial candidates with both marginalized and nonmarginalized identities are perceived as less worthy for such scholarships.…”
Section: Question 3: How Might Common Activities In Your Work Perpetu...mentioning
confidence: 99%
“…But racism may operate differently depending on the targeted group (e.g., via anti‐Blackness, xenophobia, colorism, or the model minority stereotype), and Multiracial people may additionally experience monoracism : the variant of racism that privileges monoracial identities and erases Multiracial people's experiences 25,62 . Institutional monoracism has shaped our strong preference to conceptualize race using mutually exclusive categories 62 ; it can look like electronic medical record systems that (in the 2020s, no less) are still not programmed to handle multiple race selections, 64–66 monoracially organized student recruitment and retention centers on college campuses, 62,67,68 or peer‐reviewed studies that pathologize—rather than contextualize—the impact of Multiracial identity on health 27,28,69–71 . Everyday monoracism may manifest as Multiracial microaggressions , which can look like Multiracial adolescents having to defend the “authenticity” of their racial identities to monoracial relatives or peers, 50,72–74 Multiracial people allowing others to view them as monoracial to avoid confusing or drawing unwanted attention, 62 travel security agents flagging parents of Multiracial children as suspected sex traffickers, 75 health care professionals making inappropriate assumptions or comments about a Multiracial patient's racial background, 28,76 or fetishization and exotification of a Multiracial person's physical appearances 25,73 .…”
Section: Introducing Our Critical Multiracial Theory Questions Frameworkmentioning
confidence: 99%
“…Along the same lines, an individual's self-identity is an important, yet insufficient, characteristic that contributes to how others perceive them (Brubaker 2016b). Aspects such as gender and sociocultural context additionally shape how observers classify others (Davenport 2016;Feliciano 2018;Xu et al 2021), and classifications of multiracial or racially ambiguous individuals can at times be recast into a single monoracial category (Ford, Patterson, and Johnston-Guerrero 2021;Giebel 2023;Perlmann and Waters 2002).…”
Section: Racial Classification and Appraisal Logicsmentioning
confidence: 99%